2005
DOI: 10.1161/01.atv.0000175751.30616.13
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Lecithin:Cholesterol Acyltransferase Deficiency Syndromes

Abstract: Objective-To better understand the role of lecithin:cholesterol acyltransferase (LCAT) in lipoprotein metabolism through the genetic and biochemical characterization of families carrying mutations in the LCAT gene. Methods and Results-Thirteen families carrying 17 different mutations in the LCAT gene were identified by Lipid Clinics and Departments of Nephrology throughout Italy. DNA analysis of 82 family members identified 15 carriers of 2 mutant LCAT alleles, 11 with familial LCAT deficiency (FLD) and 4 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 22 publications
8
91
0
1
Order By: Relevance
“…6 In FLD, plasma LCAT is either absent or completely lacks catalytic activity, whereas in fish-eye disease, the mutant LCAT exerts partial LCAT activity (i.e., it fails to exert activity on the HDL lipids, but esterifies cholesterol bound to apoB-containing lipoproteins). 7 Therefore, homozygous patients for FLD gene mutation exhibit more severe clinical manifestations, such as normochromic anemia and renal failure. 3 Renal disease is the major cause of morbidity and mortality in patients with FLD.…”
mentioning
confidence: 99%
“…6 In FLD, plasma LCAT is either absent or completely lacks catalytic activity, whereas in fish-eye disease, the mutant LCAT exerts partial LCAT activity (i.e., it fails to exert activity on the HDL lipids, but esterifies cholesterol bound to apoB-containing lipoproteins). 7 Therefore, homozygous patients for FLD gene mutation exhibit more severe clinical manifestations, such as normochromic anemia and renal failure. 3 Renal disease is the major cause of morbidity and mortality in patients with FLD.…”
mentioning
confidence: 99%
“…Compared to LDL from control subjects, LDL particles from carriers of two mutant LCAT alleles are smaller (12), have an abnormal composition (poor in cholesteryl esters and rich in TG and phospholipids) (38), and are more easily oxidized. Oxidation results in a cytotoxic LDL with pro-inflammatory and atherogenic properties.…”
Section: Discussionmentioning
confidence: 96%
“…In a large series of LCAT-deficient subjects, Calabresi et al (12) demonstrated that HDL particle size distribution in carriers of two mutant LCAT alleles is characterized by the lack of particles in the HDL 2 size range and the presence of a single HDL 3 subpopulation of particles, with an average size smaller than that of control HDL 3 . This is in agreement with our findings of reduced large HDL and increased small HDL subclasses, and lower HDL size in the homozygous and the Table III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCAT aktivitesi ise yoktur. Bir çalış-mada LCAT mutasyonu olan (homozigot / "compound" heterozigot) 19-70 yaş arası, 4'ü FED, 11'i klasik, LCAT eksikliği tanılı 15 erişkin hasta incelenerek, koroner kalp hastalığı (%0), hipertansiyon (%30), korneal opasite (%100), anemi (%80), böbrek hastalığı (%60) oranında saptanmıştır (36) . Tedavide total kolesterol ve trigliserit düzeyleri yüksek hastalarda hastalarda plazma lipid düzeyini düşürmeye yönelik tedavinin böbrek hastalığının ilerlemesine engel olabileceği düşünülüyor.…”
Section: C) şIlomikron Retansiyon Hastalığıunclassified